(untitled) (Anclajes, 2024)
The trip to the United States involved Martí in a journey to another language. To adapt himself to the new space that welcomed his long exile in the U.S., he had to acquire the language that he had once called “barbaric,” English. This article explores not only the translations José Martí made of those who, either as precursors, founders or followers were linked to the Transcendentalist circle, but also their thoughts about the mechanisms involved in the translation process. From his definition, in the sense that translating is transpensar a paper, it is that Martí´s translation style and the new perspective that it brings to the original work are considered. Finally, the study of those translations is essential to set up a thinking network among Martí, Emerson and Whitman and, thus, to complicate and reconsider the influence that a tradition of Anglo-Saxon origin had on the development of Martí’s literature and thought.